An Evaluation of Drug Information Services at the "IAF" Pharmacy in Makassar City - Murniati, Murniati; AR, Nurul Izza; Rahmawati, A. (Jurnal Farmasi Sandi Karsa, 2023)
Drug information services are activities carried out by pharmacists in providing impartial drug information, evaluated critically and with the best evidence in all aspects of drug use to other health professionals, patients or the public. Information about drugs including prescription drugs, over-the-counter drugs and herbs. The aim of the research is to find out drug information services at the "IAF" pharmacy in Makassar city. The research method used is a descriptive survey. Sampling in this study by purposive sampling technique. The population in the study were all "IAF" pharmacy staff in May-June 2021. The results showed that the evaluation of drug information services at the "IAF" pharmacy in Makassar city in implementing PERMENKES No.73 of 2016 in drug information services such as answering oral and written questions, providing information and education to patients, providing knowledge and skills to students who are practice, conducting research on drug use and conducting quality assurance programs have been carried out in accordance with PERMENKES No. 73 of 2016 concerning drug information service standards in pharmacies, while making bulletins/brochures/leaflets and writing or presenting papers in scientific forums has not been fully implemented.